Influence of age of child on differences in marital satisfaction of males and females in East Asian countries - Eiji Yamamura; Antonio R. Andrés (Economics and Econometrics Research Institute (EERI), 2011)
Using individual-level data for China, Korea, and Japan for 2006, this research examines how the age of children influences marital satisfaction for males and females in East Asian countries. Our results show that the marital satisfaction of males is barely affected by a child of the relationship, whereas the marital satisfaction of females with a young child is lower than that of females who do not have a child. This result holds for countries at different development stages. There is also a gender differential regarding the effect of young children on marital satisfaction. Furthermore, the more developed the country, the greater this difference becomes.
Keywords: D19; J13; J16; 330; Marital satisfaction; child; East Asian countries; ordered probit